2005
DOI: 10.5465/amj.2005.17407912
|View full text |Cite
|
Sign up to set email alerts
|

Industry Change Through Vertical Disintegration: How and Why Markets Emerged in Mortgage Banking

Abstract: This paper provides an inductive theoretical framework that explains how and why vertical disintegration happens, showing that transaction costs are an incidental feature of industry evolution. I find that gains from intrafirm specialization set off a process of intraorganizational partitioning, which simplifies coordination along parts of the value chain. Likewise, latent gains from trade foster interfirm cospecialization, which leads to information standardization. Given standardized information and simplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
319
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 390 publications
(337 citation statements)
references
References 83 publications
10
319
0
8
Order By: Relevance
“…It is well known that firms' decisions to integrate or specialize, when widely adopted, lead to vertically integrated or horizontally layered industry structures (see, for example, Baldwin and Clark, 2000;Jacobides, 2005;and Fixson and Park, 2008). However, studies at the firm level, starting with Harrigan (1985), have shown that the boundary and scope decisions of firms are often more complex than simply to integrate or specialize.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that firms' decisions to integrate or specialize, when widely adopted, lead to vertically integrated or horizontally layered industry structures (see, for example, Baldwin and Clark, 2000;Jacobides, 2005;and Fixson and Park, 2008). However, studies at the firm level, starting with Harrigan (1985), have shown that the boundary and scope decisions of firms are often more complex than simply to integrate or specialize.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies at the sector level have explored how the internal boundaries of industries change and how intermediate markets emerge or disappear (Baldwin and Clark, 2000;Jacobides, 2005;Fixson and Park, 2008). Drawing on the engineering and product design literatures, defined "industry architecture" as a somewhat stable but evolving set of relationships that organize production and innovation processes in a sector.…”
Section: Sector-level Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have used the related bicycle industry for insightful studies (Randall and Ulrich 2001;Ulrich and Ellison 2005). Finally, despite the significant changes in product architecture and industry composition, this industry exhibited a relatively stable industry boundary during the study period which enables better control for industry-level factors on competition (Dalziel 2005;Jacobides 2005). …”
Section: Industry Selection and Data Sourcesmentioning
confidence: 99%
“…A substantial literature body suggests that many products are becoming more modular over time, and that this development is often associated with a change in industry structure towards higher degrees of specialization (Sanchez and Mahoney 1996;Langlois 2002;Jacobides 2005).…”
Section: Introductionmentioning
confidence: 99%